Minding the gap: access to palliative care and the homeless. Issue 1 (December 2015) - Huynh, Lise; Henry, Blair; Dosani, Naheed
Abstract Background With an ever increasing number of individuals living with chronic and terminal illnesses, palliative care as an emerging field is poised for unprecedented expansion. Today's rising recognition of its key role in patients' illnesses has led to increased interest in access to palliative care. It is known that homelessness as a social determinant of health has been associated with decreased access to health resources in spite of poorer health outcomes and some would argue, higher need. This article aims to discuss the current state of affairs with regards to accessing palliative care for the homeless in Canada. Discussion Recent review of the literature reveals differential access to palliative care services and outcomes with differing socio-economic status (SES). Notably, individuals of lower SES and in particular, those who are homeless have poorer health outcomes in addition to poor access to quality palliative care. Current palliative care services are ill equipped to care for this vulnerable population and most programs are built upon an infrastructure that is prohibitive for the homeless to access its services. A preliminary review of existing Canadian programs in place to address this gap in access identified a paucity of sporadic palliative care programs across the country with a focus on homeless and vulnerably-housed individuals. It is apparent that there is no unified national strategy to address this gap in access. Summary The changing landscape of the Canadian population calls for an expansion of palliative care as a field and as many have put it, as a right. The right to access quality palliative and end of life care should not be confined to particular population groups. This article calls for the development of a unified national strategy to address this glaring gap in our healthcare provision and advocates for attention to and adoption of policy and processes that would support the homeless populations' right to quality palliative care.